Neotropical Scolopini (Heteroptera: Anthocoridae): new taxa, diagnostic characters and a key to the genera of the tribe - Carpintero, Diego Leonardo (2012)
The tribe Scolopini is characterized by having males with the uradenia consisting of paired glands with either a single or paired openings on abdominal sternum III or IV (exceptionally on V), and females with copulatory tubes (not in Calliodina), and a midventral abdominal copulatory site. The tribe is composed by two subtribes, Scolopina with four genera and Calliodina with seven genera. Two new genera of Scolopini are proposed: Guayascoris foreroi, a new genus and species of Calliodina from Ecuador, and Ameroscolopa a new genus of Scolopina including the two American species of Scoloposcelis Fieber, 1864: Ameroscolopa flavicornis (Reuter, 1871) comb. nov. and A. basilicus (Drake & Harris, 1926) comb. nov. Diagnostic characters, geographic distribution, species included, and a key to the recognition all the Neotropical genera of the tribe are also given.